Accidental Extrusion of Calcium Hydroxide into the Inferior Alveolar Canal during Endodontic Treatment: A Case Report - Supratim Tripathi; Payal Tripathi; Pradyumna Misra; Divyanu (Journal of Pharmacy and Bioallied Sciences)
In a root canal treatment technique, calcium hydroxide paste is often used as an intracanal medication. When treating mandibular molars, there is a possibility that calcium hydroxide may inadvertently protrude beyond the apex, injuring the inferior alveolar nerve and producing symptoms like paresthesia or persistent inflammation. The extrusion of calcium hydroxide and nonsurgical therapy is described in this case study.